Evaluation of the interactions between human cells and silicone rubber surfaces modified by Atom Transfer Radical Polymerization - Leirós, Ana Catarina Correia (2011)
Dissertação de mestrado integrado em Engenharia Biomédica (área de especialização em Engenharia Clínica)